Public policy about advanced courses to repeaters in secondary education, Costa Rica: case study - Abarca Rodríguez, Allan (2015)
In 2009, in Costa Rica begins the execution of the secondary school promotion system´s upgrade approved in 2008 by the Higher Education Council: Student who unapproved subjects have a duty to enroll in the next year but they have a right to register the subjects in the next level (for which already approved the requirement). This article is the result of a research in which analyze the opinion’s actors in a secondary school about the effects of public policy in practice, its positive and negative aspects and public policy´s general conception for its validity. In total, 66 people were interviewed: 25 students who advanced courses of them, 25 teachings, 12 students of high academic performance and 4 union leaders. On the other hand, it concludes that it generated a high academic and administrative complexity with unwanted academic impacts, this implies the policy´s high inceptive legitimacy –considered fair- is in issue by execution´s sensitives negatives consequences.